EXPLAINING MUTUAL FUND EXPENSES & FUND PERFORMANCE DIFFERENCES BETWEEN DIRECT FUNDS AND REGULAR (BROKER SOLD) FUNDS IN INDIA THROUGH STRUCTURAL EQUATION MODELLING - et. al., Ramkrishna Dikkatwar (International Journal of Modern Agriculture, 2021)
Abstract It was observed that differences in fund performance cannot be fully explained by expense differential between direct plans and regular plans (broker sold) in Indian Mutual fund (MF) industry. This study attempts to explain fund performance differential between direct plans and regular plans (broker sold). The data taken for study comprises of 528 Indian mutual funds launched on or before 31st March 2013. Proposed model to explain fund performance differential between direct plans and regular plans was tested by administering structural equation modelling (SEM) on four panels formed on the basis of fund type (i.e. debt & equity) and family ownership (bank owned and non-bank owned). The results of SEM supported hypothesized structural model for debt funds as well as equity funds offered by bank owned MF families but not for funds offered by non-bank owned MF families. This paper shows that differential behaviors of bank owned and non-bank owned MF families in terms of portfolio management. Contrary to past research study observes negative relationship between number of funds offered by the fund family on fund expenses difference.